Penggunaan Media Metaverse Augmented Reality Terhadap Penguasaan Kosakata Bahasa Jerman - Fakhira Dzul Fadliani; Burhanuddin Burhanuddin; Muh. Anwar (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. This study aims to determine the effectiveness of using the Metaverse Augmented Reality media on the mastery of German vocabulary in class XI students at SMA Negeri 1 Pangkep. This research is a quasi-experimental with a pre and post-test control group design. The sample for this research consisted of class XI MIPA 5 students as the experimental class (24 students) and class XI MIPA 4 students (24 students) as the control class, selected using simple random sampling. Data were analyzed using t-test. The results of data analysis using the independent sample t-test showed a tcount value of 5.072 and a ttable value of 2.012 with a significance level of 0.05 and a df of 46. Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. From the results of the study, it was concluded that the use of the Metaverse Augmented Reality media was considered effective on the mastery of German vocabulary for class XI students at SMA Negeri 1 Pangkep. Keywords: Media, Metaverse Augmented Reality, Vocabulary Mastery